2016
DOI: 10.1542/peds.2015-3023
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Process for ED UTI Screening in Febrile Young Children: Reducing Catheterization Rates

Abstract: BACKGROUND AND OBJECTIVES: Urinary tract infection (UTI) screening in febrile young children can be painful and time consuming. We implemented a screening protocol for UTI in a high-volume pediatric emergency department (ED) to reduce urethral catheterization, limiting catheterization to children with positive screens from urine bag specimens. METHODS: This quality-improvement initiative was implemented using 3 Plan-Do-Study-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…A pproximately 7% of children younger than 2 years who present to an emergency department with fever have a urinary tract infection (UTI). 1,2 However, testing for UTI in young children, whether by catheterization or via the 2-step process (testing bag specimens first and limiting catheterization to children with positive results), 3,4 is challenging. Accordingly, clinicians obtain samples only when they judge the probability of UTI to be sufficiently high.…”
mentioning
confidence: 99%
“…A pproximately 7% of children younger than 2 years who present to an emergency department with fever have a urinary tract infection (UTI). 1,2 However, testing for UTI in young children, whether by catheterization or via the 2-step process (testing bag specimens first and limiting catheterization to children with positive results), 3,4 is challenging. Accordingly, clinicians obtain samples only when they judge the probability of UTI to be sufficiently high.…”
mentioning
confidence: 99%
“…On the other hand, leukocyte contamination can result in a false-positive result. Although urine bag can be used in certain settings for a first step screen 20 , bagged urine tends to be contaminated with leukocytes from around the perineum as well as from first-pass urine. Diaper urine is less likely to be contaminated by perineal leukocytes because urine is immediately absorbed after urination by the diaper's superabsorbent polymers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also revealed benefit in the use of clinical pathways for the reduction of unnecessary testing or interventions in pediatrics, including reducing broad-spectrum antibiotic use for pneumonia, computed tomography scans for appendicitis and head injury, catheterization to test for UTIs, and decreased use of antibiotics for lowrisk febrile infants. 22,25,[32][33][34] The implementation of the clinical pathway reduced ED LOS for patients who were discharged from the ED. Factors that may have contributed to this include earlier initiation of workup by residents due to comfort with pathways and order sets, reduced time spent on LPs and antibiotic administration, and earlier disposition due to the standardization of risk-stratification and admission criteria.…”
Section: Figurementioning
confidence: 99%